The Struggles of Audrey Against Her Anxiety Disorder in The Novel Finding Audrey by Sophie Kinsella: Anxiety Disorder - Hasni; Dahlan, Sandra Dewi; Darmadali, Waode Surya (Journal of Islamic Culture and Literature (JICeL), 2023)
This research discussed the struggles of Audrey against her anxiety disorder in the novel Finding Audrey by Sophie Kinsella. This study aimed to describe the triggers of Audrey’s anxiety and to explain the internal and external conflicts reflected in the novel. This research used psychoanalysis theory by Sigmund Freud and the internal and external conflicts theory by Robert Stanton. This research used qualitative descriptive as its method. The findings showed that Audrey were depressed as the effect of bullying. She experienced 10 of 15 acts of the action indicators of anxiety disorder. From those actions, the researcher concluded that there are two major disadvantages of having anxiety disorders found and portrayed through the main character of the novel, which are having difficulty in carrying out daily activities and inability to interact normally with others. Keywords: Anxiety Disorder, Internal Conflicts, Psychoanalysis, Finding Audrey